Agricultural marketing and price analysis - Norwood, F. Bailey (Prentice-Hall, 2008)
Written for courses in agricultural marketing, agricultural price analysis, economics of agricultural marketing, and agribusiness marketing, this text offers a contemporary treatment of all the core agricultural price analyses and marketing topics covered in these undergraduate courses. The text also covers organization economics, such as tacit collusion and empirical price analysis using regression, and consumer research. Norwood and Lusk write in an informal tone, offering many colorful examples that are familiar to today's undergraduate students.